2020
DOI: 10.1371/journal.pone.0242161
|View full text |Cite
|
Sign up to set email alerts
|

Designing better input support programs: Lessons from zinc subsidies in Andhra Pradesh, India

Abstract: India has one of the largest agricultural input support programs in the world, delivered in the form of subsidies to farmers, raising concerns about its sustainability. This paper evaluates the performance of one such support, the micronutrient subsidy program in the state of Andhra Pradesh (AP) and presents a case for providing this support in the form of direct cash transfers. Under the program, key soil micronutrients- zinc, boron, and gypsum were distributed free of cost to farmers living in micronutrient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…4 ). This can be linked to constraints such as low educational attainment of those belonging to socially marginalized communities and limited access to productive resources including credit, land and human capital ( Krishna et al, 2019 ; Gupta et al, 2020 ; Anderson et al, 2006 ). However, in Dang, we find no ethnicity-based differences in primary source of agriculture information between the two predominant communities in our sample- Chhetris and Janjati (tribals).…”
Section: Resultsmentioning
confidence: 99%
“…4 ). This can be linked to constraints such as low educational attainment of those belonging to socially marginalized communities and limited access to productive resources including credit, land and human capital ( Krishna et al, 2019 ; Gupta et al, 2020 ; Anderson et al, 2006 ). However, in Dang, we find no ethnicity-based differences in primary source of agriculture information between the two predominant communities in our sample- Chhetris and Janjati (tribals).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it forces strict rationing that often leads to its suboptimal allocation. For example, a recent study in Andhra Pradesh showed that an adequate amount of the free Zn is distributed to traditionally prosperous irrigated districts in contrast to regions where Zn deficiency is high [135]. Second, distributing subsidized or free Zn by the government crowds out commercial demand.…”
Section: Policy Options For Scaling Zn Biofortification Of Ricementioning
confidence: 99%
“…To what extent agricultural growth is responsive to the provision of subsidies is an important research question as subsidies are often criticized for being less productive, poorly targeted, market distorting, financially and environmentally unsustainable and so on (Fan et al. , 2008; Gulati and Banerjee, 2016, 2018; Gupta et al., 2020; Akber and Paltasingh, 2020; Tandon and Aggarwal, 2021). As per Central Statistical Office, growth of the agricultural sector decelerated sharply following the reform period where 4.78% per annum growth achieved during eighth five-year plan (1992–1993 to 1996–1997) reduced to just 2.7% per annum during the last 12th five-year plan (2012–2013 to 2016–2017).…”
Section: Introductionmentioning
confidence: 99%